1986
DOI: 10.1111/j.1365-2125.1986.tb05206.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and the pharmacodynamics of angiotensin converting enzyme inhibitors enalapril and enalaprilat.

Abstract: The effect of age on the pharmacodynamic responses to converting enzyme inhibitors, enalapril and enalaprilat was investigated in nine young (22‐30 years) and nine sex‐matched elderly (65‐73 years), healthy volunteers. The groups differed in baseline blood pressure, young 121/64 mmHg, elderly 142/75 mmHg (P less than 0.01), but not in sodium intake or body weight. Both enalapril and enalprilat produced significant falls in blood pressure in both groups but no increase in heart rate in the supine or erect postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…The findings of reduced clearance, greater AUC and reduced distribution volume may partly explain the greater hypotensive effect and prolonged converting enzyme inhibition we have observed in elderly subjects (Ajayi et al, 1986). We detected no age related alteration in the sensitivity of plasma ACE to inhibition.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The findings of reduced clearance, greater AUC and reduced distribution volume may partly explain the greater hypotensive effect and prolonged converting enzyme inhibition we have observed in elderly subjects (Ajayi et al, 1986). We detected no age related alteration in the sensitivity of plasma ACE to inhibition.…”
Section: Discussionsupporting
confidence: 48%
“…We detected no age related alteration in the sensitivity of plasma ACE to inhibition. Thus, sensitivity of ACE is unlikely to underlie the pharmacodynamic differences observed between the two groups (Ajayi et al, 1986). The full therapeutic implication of the findings from this single dose study must await further multiple dose studies in the elderly.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This has been postulated as being a reflection of the lower prevalence of hypertension associated with elevation of plasma renin activity in the elderly patient [4]. Based on this premise, it has been postulated that inhibitors of angio tensin-converting enzyme (ACE) would not be of particular value in treating elderly hypertensive patients [5], However, singleand multiple-dose studies with the ACE in hibitor enalapril maleate have shown that elderly patients respond with a greater fall in BP than do younger patients, although, when corrected for the higher starting BP in the elderly patient, the effect may be similar [6,7], The ACE inhibitors enalapril and lisinopril have both been shown to have significant anti hypertensive activity in elderly patients with hypertension [8. 9], although no direct com parisons across the entire age spectrum have been performed.…”
mentioning
confidence: 99%
“…However, it is now apparent, both from small, detailed studies of the kinetics and dynamics of ACE inhibi tors in older subjects [23][24][25] and from ex tensive clinical experience, that these drugs are effective and well tolerated either alone or in combination with diuretics in the el derly [26,27], Minor age-related pharmaco kinetic differences have been reported. These include a predictable reduction in elimination by the kidney [23] and minor changes in distribution, volume, and bio availability [25], The magnitude of blood pressure fall after acute dosing may be greater in elderly normotensive subjects than in the young [24,25]. Interpreting these re sults poses some difficulty because of differ ent baseline values and the fact that the per centage change in blood pressure may be the same.…”
Section: Ace Inhibitors In the Elderlymentioning
confidence: 99%